Scientific Workshop Proceedings of the XP2015 2015
DOI: 10.1145/2764979.2764985
|View full text |Cite
|
Sign up to set email alerts
|

A reflection on agile requirements engineering

Abstract: The software development industry has rapidly accepted agile methods. Empirical studies suggest that due to their flexible and emergent nature, agile methods brought solutions to several chronic problems of traditional software development methods. One among the many is the acceptance of requirements changes at later stages of development. However, knowledge about the solutions that agile brought to requirements engineering (RE) is fragmented. Also, little is known about whether the agile philosophy, while int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have reported the engineering of QRs in Agile as a challenge [3][4] [5][8] [9]. Other studies indicated the lack of empirical studies regarding Agile QRs [5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the engineering of QRs in Agile as a challenge [3][4] [5][8] [9]. Other studies indicated the lack of empirical studies regarding Agile QRs [5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent SLR [6] on engineering QRs indicated the lack of empirical research specifically devoted to the challenges that Agile practitioners face when dealing with QRs as a whole in ALSD [6]. However, there are studies reporting Agile RE challenges [5][8][9] [3], which we summarize as follows: The SLR of Inayat et al [5] focused on the differences between traditional and Agile RE and the challenges of Agile RE. These authors identified seven challenges brought by Agile, one of…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional RE is facing many a challenges such as communication gaps, over scoping, requirement prioritization, validation and customer involvement [45]. These issues are resolved by Agile practices such as face to face communication for minimizing documentation and communication gaps, gradual detailing of requirements for reducing over scoping, requirement prioritization by customer based on the worth of business to deal with requirements validation and close interaction on the part of team and customer in order to avoid lack of customer participation [46]. Issues caused by the traditional RE and the solutions provided by the Agile RE are described in Table 2.…”
Section: Re In Agile Vs Re In Waterfall Methodsmentioning
confidence: 99%
“…User stories generation is an ongoing process in the XP iterative approach. Therefore, involving the customer in user story creation and gathering also ease the chances of incoming change requests (Inayat et al 2015). To make a realistic customer expectation from the output of each iteration, we recommend including 'empathy' and 'define' practices of DT along with user 'persona' to create a DT-user story.…”
Section: Dt Integration In Xp Exploration Phasementioning
confidence: 99%